Analyzing the Economic Impact of Public Share Ownership, Capital Structure, and Environmental Costs on Financial Performance with Good Corporate Governance as a Moderating Variable - Mahadewi, Gusti Ayu Putu Agung; Werastuti, Desak Nyoman Sri; Purnamawati, I Gusti Ayu (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze and find out public share ownership has a positive effect on financial performance, to analyze and find out capital structure has a positive effect on financial performance, to analyze and find out environmental costs have a positive effect on financial performance, to analyze and find out GCG is able to moderate the effect of public share ownership on financial performance, to analyze and find out GCG is able to moderate the effect of capital structure on financial performance, to analyze and find out GCG is able to moderate the effect of environmental costs on financial performance. This research is quantitative research. This study shows that Public Share Ownership, Capital Structure, and Environmental Costs have a positive and significant effect on the financial performance of property and real estate sector companies on the IDX in 2020-2022. In addition, Good Corporate Governance (GCG) is proven to moderate the relationship between these three variables and financial performance, thereby strengthening their positive influence. These findings support stakeholder, agency, and legitimacy theories.